THE ROLE OF DANCE MOVEMENT THERAPY IN THE TREATMENT OF DEPRESSION: AN OVERVIEW OF RECENT EVIDENCE - Ida Dunder; Mateusz Biszewski; Elżbieta Bebrysz; Jan Palmi; Karolina Dębek-Kalinowska; Piotr Bartnik; Jarosław Baran; Magdalena Koss; Aleksandra Drabik; Weronika Ziomek (International Journal of Innovative Technologies in Social Science, 2025)
Background: Depression is a widespread mental disorder affecting approximately 280 million people worldwide. While pharmacological treatments and cognitive-behavioral therapy (CBT) are considered first-line interventions, there has been growing interest in recent years in complementary, non-pharmacological therapies, such as Dance Movement Therapy (DMT), which offers a holistic, body-centered approach to improving mental health outcomes.Aim: This review aims to evaluate the current evidence on the effectiveness of Dance Movement Therapy (DMT) in the treatment of depression. It seeks to understand the mechanisms through which DMT exerts its effects and to identify specific populations that may benefit most from this intervention.Methods: A literature review was conducted using PubMed and Google Scholar databases, covering the years 2015 to 2025.Results: DMT has demonstrated positive effects on depressive symptoms across various populations. Improvements were noted not only in mood but also in cognitive functioning, physical health, interpersonal relationships, and emotional regulation. While effect sizes varied, consistent within-group improvements and high adherence rates were observed.Conclusion: DMT is a safe, engaging, and potentially effective adjunctive treatment for depression, especially when personalized and delivered by trained professionals. Its multicausal mechanism of action makes it a valuable tool in the integrative treatment of depressive disorders. Further high-quality, randomized studies are needed to establish standardized clinical guidelines.